2021
DOI: 10.1093/dote/doab027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of standardized clinical pathways on esophagectomy: a systematic review and meta-analysis

Abstract: Summary Esophageal surgery is historically associated with adverse postoperative outcomes. Selected high-volume centers have previously reported the effect on clinical outcomes following the adoption of a standardized clinical pathway (SCP). This meta-analysis aims to evaluate the current literature to document the effect of SCP and enhanced recovery after surgery (ERAS) on esophagectomy outcomes. A literature search was conducted through the main search engines (PubMed, Embase, Medline, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Firstly, due to the study design, the hospital length of stay could be subjective and influenced by an individual surgeon’s perspective. Secondly, we did not examine how each pathway contributed to acceleration of recovery; therefore, a standardized ERAS pathway in esophagectomy would be required in future studies [ 43 ]. Thirdly, this study did not evaluate the long-term effect of ERAS on esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, due to the study design, the hospital length of stay could be subjective and influenced by an individual surgeon’s perspective. Secondly, we did not examine how each pathway contributed to acceleration of recovery; therefore, a standardized ERAS pathway in esophagectomy would be required in future studies [ 43 ]. Thirdly, this study did not evaluate the long-term effect of ERAS on esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (26 articles; 5 RCT and 6 prospective trials) has assessed the collective reported experience with standardized clinical pathways before the introduction of the esophagectomy-specific ERAS consensus guidelines [11]. This meta-analysis confirmed significant improvements in pulmonary complication (34% reduction) and hospital LOSalthough no difference in overall morbidity, post-operative mortality or readmission rates was identified (Table 1).…”
Section: Evolution and Impact Of Eras Programs On Post-operative Outc...mentioning
confidence: 91%
“…This meta-analysis confirmed significant improvements in pulmonary complication (34% reduction) and hospital LOSalthough no difference in overall morbidity, post-operative mortality or readmission rates was identified (Table 1). However, from the analysis of the studies included in this publication, it is clear that there is a great variability of protocols and only few ERAS elements such as the use of epidural analgesia, jejunostomy placement, start enteral feeds and mobilization ≤ 1 day, start soft solid diet ≤ 4 day and chest tube removal ≤ 5 day were widely utilized (> 50% of the studies) [11].…”
Section: Evolution and Impact Of Eras Programs On Post-operative Outc...mentioning
confidence: 99%
See 2 more Smart Citations